Improved adaptive mesh refinement for conformal hexahedral meshes. (December 2016) - Nicolas, Gérald; Fouquet, Thierry; Geniaut, Samuel; Cuvilliez, Sam
Highlights: The conformal refinement of a mesh made of hexahedra is available. The conformal transition is made by a combination of pyramids and tetrahedra. A set of 47 patterns was designed to solve any conflict about the pending nodes. The efficiency of the method is shown with the mechanical simulation of a crack. Abstract: The h-refinement is a technique to achieve the mesh adaptation during a finite element simulation. Some elements are selected because the error is higher than a given threshold: they are split. This operation creates new elements where the size of the edges is divided by 2 in the zone of high error. To produce a conformal mesh, the connection between two zones with different levels of refinement must be examined. This paper proposes a solution in the case of meshes made of hexahedra. Depending on the type of interface, a set of patterns has been designed. In each pattern, the hexahedron is split into pyramids and tetrahedra. That specific splitting stops the propagation of the refinement and allows h-refinement in numerical simulations based on hexahedra with a conformal finite element method. At the end, an application to a crack analysis is shown.